What are the Spratly Islands? - Hutchison, C.S.; Vijayan, V.R. (Elsevier, 2010)
Seismic records, combined with dredged samples and a core, indicate that the Spratly Islands of the Dangerous Ground Province are constructed of presently active carbonate build-ups, known to extend back continuously at least to the Pleistocene and presumed to have initiated in the Miocene, most likely upon the crests of sea-floor cuestas that trend north-east-south-west parallel to the sea-floor spreading magnetic anomalies of the contiguous abyssal plain of the southern part of the South China Sea. The cuestas range from spectacular to subdued, constructed of Triassic and Cretaceous strata and no older rocks have been identified from dredges. The cuesta axes plunge towards the south-west away from the islands, suggesting that the reefs began colonising their more elevated parts, but the timing is uncertain. The highest seismically recorded cuesta crest is in 440 m of water and the islands and reefs are generally closely surrounded by water deeper than 1500 m. Since the so-called Mid-Miocene Unconformity (MMU), the region has been undergoing post-rift thermal subsidence. However, the nearby seismic lines show no evidence of drowned carbonate reefs. It is suggested that the coral-algal reefs colonised the crests of the most elevated cuestas that have maintained stability as shown by the 165 m core of one reef indicating periodic exposure with caliche horizons. Deepening water has protected the build-ups from extinction by post-rift draping strata in contrast to the Central Luconia Province, and the build-ups have been able to keep up with regional thermal subsidence. The dredged Mesozoic strata indicate that the Dangerous Ground is not exotic and should be interpreted as an integral part of the pre-rift Sundaland continent that included South China, Vietnam, Peninsular Malaysia, western Sarawak and possibly part of Sabah. Igneous and metamorphic samples have been dredged. Although individual spot K/Ar dates cannot be accepted at face value, such rocks can also be interpreted as an integral part of Sundaland. Post-MMU dredged samples are predominantly deep-water calcareous mudstones typified by the draping strata of the Ocean Drilling Program (ODP) Site 1143 cored from Recent to Late Miocene. (C) 2010 Elsevier Ltd. All rights reserved.